JADWAL WAKTU SALAT ABADI - Jayusman, Jayusman (The Pontianak State Institute of Islamic Studies, 2013)
The all time, perpetual or all year round prayer schedule so it is called because the schedule can be used for a very long period of time. Even for centuries, this schedule is still accurate. The schedule is usually disputed by the Falak experts with regard to certain time zones that need to be adjusted.